Negative self-assessment revisited: Exchange of reason for the evaluation to make congruent understanding visible in Japanese conversation - Sekizaki, Hironori (East Asian Pragmatics, 2024)
This study aims to explore the fundamental and necessary unit in discourses that initiate with negative self-assessment. Since past research has mainly focused on the second assessment as a response to the negative self-assessment as the first assessment, it remains unclear how conversations progress beyond the second assessment. Data for the study were collected from a corpus of 20 same-gender Japanese dyad conversations between undergraduate students who had close relationships with each other. The participants talked about “areas that I am not good at or find difficult”. The study found that the participants typically exchanged rationales for the negative self-assessment and reached a consensus on their views regarding the assessment. The study concluded that confirming both sides’ views was prioritised over formally denying the negative self-assessment, and such confirmation was essential for gradually forming a consensus among the speakers.